Estimation of seasonal influenza vaccine effectiveness using data collected in primary care in France: comparison of the test-negative design and the screening method. (April 2018) - Vilcu, A.M.; Souty, C.; Enouf, V.; Capai, L.; Turbelin, C.; Masse, S.; Behillil, S.; Valette, M.; Guerrisi, C.; Rossignol, L.; Blanchon, T.; Lina, B.; et al.
Abstract: Objectives: We discussed which method between the test-negative design (TND) and the screening method (SM) could provide more robust real-time and end-of-season vaccine effectiveness (VE) estimates using data collected from routine influenza surveillance in primary care. Methods: We used data collected during two influenza seasons, 2014–15 and 2015–16. Using the SM, we estimated end-of-season VE in preventing medically attended influenza-like illness and laboratory-confirmed influenza among the population at risk. Using the TND, we estimated end-of-season VE in preventing influenza among both the general and the at-risk population. We estimated real-time VE using both methods. Results: For the SM, the overall adjusted end-of-season VE was 24% (95% confidence interval (CI), 16 to 32) and 12% (95% CI, −16 to 33) during season 2014–15, and 53% (95% CI, 44 to 60) and 47% (95% CI, 23 to 64) during season 2015–16, in preventing influenza-like illness and laboratory-confirmed influenza, respectively. For the TND, the overall adjusted end-of-season VE was −17% (95% CI, −79 to 24) and −38% (95% CI, −199 to 13) in 2014–15, and 10% (95% CI, −31 to 39) and 18% (95% CI, −33 to 50) in 2015–16, among the general and at-risk population, respectively. Real-time VE estimates obtained through the TND showed more variability across each season and lower precision than those estimated with the SM. Conclusions: Although the worldwide use of the TND allows for comparison of overall VE estimates among countries, the SM performs better in providing robust real-time VE estimates among the population at risk.